Cognições parentais: crenças, metas e estratégias de socialização de mães primíparas - SILVA, Raimundo Arão (2008)
The literature about parental cognitions has been indicating that mothers of different contexts and with differences in the education level tend to differ as the valorization of socialization goals: the mothers from countries western and urban centers emphasize goals of related selfmaximization, while the mothers of cultures no western tend to emphasize goals of proper demeanor. The literature has also been indicating that the Brazilian mothers tend to be heterogeneous regarding emphasis given on the categories of socialization goals. The present study was based on that literature and had as objective investigates the parental cognitions in mothers from two different contexts. The sample was formed by 100 mothers primiparous, being 50 from urban context and 50 from no-urban context. The participants answered the Questionnaire of Beliefs about maternal practices and the Interview on Goals Socialization. The data were analyzed in agreement with the categories proposed by the authors of the instruments. The results indicated that the mothers from two contexts differed in the age, education level, value of the scores in the evaluation of practices and levels of verbal fluency in the regarding answers the goals and socialization strategies. The level of maternal education was correlated positively with the age, with the scores of the evaluation of the practices and with the verbal fluency. It was verified that the mothers of the two contexts resemble each other as for the level of importance attributed the some practices, but they differ in relation to other and that they present the same order of valorization of the dimensions of beliefs. They were also identified significant differences in the emphasis on the selfmaximization goals and of propper demeanor and in the dimensions individualist and sociocentric. In relationship the socialization strategies were verified that the mothers from two contexts gave larger emphasis on the strategies centered in the context, and the mothers of urban context stood out in this emphasis. Some of the hypotheses of the study were confirmed. The found results corroborate data of the national literature that has indicated that the mothers from Belém emphasize the selfmaximization categories and proper demeanor identically, suggesting an inclination for a autonomous relational model. These results contribute to the enlargement of the understanding of the Brazilian mothers' cognitions and to strengthen the evidence of the effects of the context and of the education about the parental cognitions.